The Effects of Oil Spills on Phytoplankton in an Arctic Lake and Ponds - Miller, Michael C.; Alexander, Vera; Barsdate, Robert J. (ARCTIC, 1978)
The effect of oil spilled on Alaskan freshwater phytoplankton populations was studied in waters affected by natural oil seeps, by controlled crude oil spills in tundra thaw ponds and in a morainal lake, by subpond manipulations and bioassay experiments. The studies were carried out over a period of seven years. Regardless of dose the effects of oil were predictable in the small ponds. The zooplankton populations were virtually eliminated, and after an initial depression of primary productivity the photosynthetic rates returned to approximately prespill levels with a small increase in algal biomass. A markedly altered algal composition was an invariable effect of the response, with the elimination of a dominant flagellated form, Rhodomonas spp., in the case of the ponds. From the results of subpond manipulation experiments, evidence supports the hypothesis that elimination of grazers is the principal cause of altered species composition and increased biomass in these ponds. In our lake system there was a severe reduction in primary production during the season of the experimental spill. During the second year only the spring boom was suppressed by the added oil. Bioassay experiments supported the hypothesis that in such lakes, direct inhibition of algal photosynthesis may be important, although zooplankton were greatly reduced.